Non-linear finite element analysis of steel fibre self compacting reinforced concrete beams - Melan, Aisyahira (2018)
Steel fibre reinforced concrete (SFRC) may be defined as a composite material made with portland cement, aggregate, and incorporating discrete discontinuous fibres. The role of randomly distributed discontinuous fibres is to bridge across the cracks which provide post-cracking ductility. Through this study, the models of reinforced concrete (RC) beam were developed by using finite element method to observe and simulate the behaviour of RC beam in terms of cracking pattern and the relationship between shear and deflection. The data on mechanical properties such as tensile strength, compressive strength and flexural strength were adopted from the previous study. By using LUSAS Software, a nonlinear analysis is carried out where three beams were modelled considering the different type of concrete mix namely Normal Concrete (NC), Self Compacting Concrete (SCC) and Steel Fibre Self Compacting Concrete (SFSCC). SFSCC was used where the stirrups were reduced to 50% in order to study the possibility of steel fibre to partly replaced normal stirrups. The analysis observed that the addition of 1% steel fibre by volume in plain concrete with the same number of stirrups produced 37.1% increment in ultimate shear load resistance compared to control sample (NC125). Meanwhile, an appreciable increase in strength was also recorded for the beam with increased stirrups spacing, which is 31.8%. The addition of steel fibre in the concrete mix also improved the ultimate deflection of the beam in the range of 15.6% and 35%. The comparative study between Finite Element Analysis (FEA) and the experimental result showed a small difference range, between 8% and 18%, thus, proving the numerical prediction using LUSAS software.